WEB APPLICATION DEVELOPMENT WORKSHOP ON MANDIRI MOTOR USING PHP, MySQL & MACROMEDIA DREAMWEAVER 8.0 - Andri Asmawi (Jurnal Sistem Informasi, 2009)
In the development of information technology is so rapid now more easy for every person in getting information. The information can be obtained in many ways, especially in the automotive world that is growing rapidly. Therefore a car repair service business / workshop called Independent Motor offers easy to repair and treat your vehicle with the product-product of our best service. You can also make reservations online service for product our service Services Booking facility.